Combined transcriptomic and metabolomic analysis of the mechanism by which Bacillus velezensis induces resistance to anthracnose in walnut - Wang, Linmin; Zhu, Tianhui (Frontiers in Microbiology, 2024)
Walnut (Juglans spp.), a significant deciduous tree of economic and ecological importance, faces substantial threats from walnut anthracnose, primarily caused by Colletotrichum gloeosporioides. Bacillus velezensis has shown promise in mitigating this fungal pathogen. To delve deeper into the induction mechanism of B. velezensis on walnut plant resistance, we conducted a metabolomic analysis on walnut leaves from six different treatment groups. Specifically, the groups were defined as follows: Group B.v. was inoculated with B. velezensis alone, Group CK served as the blank control, and Group C.g. was inoculated solely with C. gloeosporioides. Group B.v.−C.g. received B. velezensis followed by C. gloeosporioides inoculation. Group B.v.+C.g. underwent simultaneous inoculation with both B. velezensis and C. gloeosporioides, while Group C.g.−B.v. was treated first with C. gloeosporioides then B. velezensis. A total of 1,503 metabolites were detected, mainly including flavonoids, terpenoids, and steroids. The results revealed that B. velezensis spraying not only enhanced the inherent resistance of walnut plants but also significantly regulated walnut plants already infected with C. gloeosporioides. This was mainly achieved by inducing walnut plants to adjust their metabolic pathways such as salicylic acid, jasmonic acid, and abscisic acid, thereby strengthening their stress response. Transcriptomic and metabolomic correlation analyses showed that in the comparisons of B.v. vs. CK, C.g. vs. CK, and C.g.−B.v. vs. C.g., 59, 244, and 122 differential abundance metabolites were detected, along with 7860, 3677, and 5587 differential genes, respectively. Amino acid synthesis, starch and sucrose metabolism, photosynthesis, phenylpropane metabolism, purine metabolism, and glutathione metabolism played crucial roles in walnut’s disease resistance mechanism. Further analysis revealed that B. velezensis induced walnut plants to regulate multiple genes, such as LOC109005403, LOC108985444 and LOC118344177, resulting in the production of defensive metabolites such as palmitic acid, coumarin and ferulic acid, thereby enhancing their resistance to C. gloeosporioides. In summary, B. velezensis induces systemic resistance in walnut plants by modulating the metabolic pathways of salicylic acid, jasmonic acid, and abscisic acid. It enhances this resistance by strengthening cell walls, synthesizing defensive secondary metabolites, and regulating energy metabolism and stress responses. These findings provide a solid theoretical foundation for the future field application of B. velezensis in controlling walnut anthracnose.